1996
DOI: 10.4315/0362-028x-59.5.551
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Carryover of Aflatoxin from Cow Feed to Milk by Addition of Activated Carbons

Abstract: According to a double-reversal experimental design on 12 late-lactation Friesian cows the effect of two activated carbons (ACs) (CAC1 and CAC2) and a hydrated sodium calcium aluminosilicate (HSCAS) on carryover of aflatoxin B1 (AFB1) from feed to aflatoxin M1 (AFM1) in milk was determined. Cows were fed a basal diet containing AFB1 naturally contaminated corn meal and copra, During week 1 cows were fed diets containing AFB1 alone (11.28 μg of AFB1/kg of feed); in week 2 the diets contained AFB1 plus 2.0% sorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 0 publications
2
34
2
1
Order By: Relevance
“…This is in accordance with Murthy and Devegowda (2004) who reported that modified glucomannan readily adsorb several mycotoxins better than inorganic binders in broilers. Similarly a 36 % reduction in carry over from AFB1 in feed to AFM1 in milk was reported in an in vivo study by Galvano et al (1996). Akhtar et al (2014) also reported its better efficacy in terms of improved hematological and biochemical parameters.…”
Section: Resultssupporting
confidence: 57%
“…This is in accordance with Murthy and Devegowda (2004) who reported that modified glucomannan readily adsorb several mycotoxins better than inorganic binders in broilers. Similarly a 36 % reduction in carry over from AFB1 in feed to AFM1 in milk was reported in an in vivo study by Galvano et al (1996). Akhtar et al (2014) also reported its better efficacy in terms of improved hematological and biochemical parameters.…”
Section: Resultssupporting
confidence: 57%
“…Previous studies have shown its effect at a high dose in goats (Hatch et al, 1982), other studies report variable results. Galvano et al (1996) showed reduced aflatoxin residues in the milk of cows consuming different sources of charcoal, but responses to charcoal did not exceed those to HSCAS. This is in line with our findings.…”
Section: Discussionmentioning
confidence: 93%
“…Variability is due to different factors such as individual response, AFB 1 intake level, stage and order of lactation [10]. Literature data about AFB 1 carry over in dairy ewes milk are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In lactating animals the conversion rate of AFB 1 to AFM 1 ranges between 0.5 and 6% [10]. Variability is due to different factors such as individual response, AFB 1 intake level, stage and order of lactation [10].…”
Section: Introductionmentioning
confidence: 99%